The Mediation of Emotion Regulation Strategies in the Relationship between Internet Addiction and Life Satisfaction during the COVID-19 Pandemic - Mehmet Ali Yıldız and Okan Uslu (Educational Process: International Journal)
Background/purpose – The research aimed to examine the mediation of emotion regulation strategies in the relationship between Internet addiction and life satisfaction during the COVID-19 Pandemic.